Exploring consumer motivation and decision-making in accommodation rentals through peer-to-peer digital platforms - Pilvinen, Linda (My University, 2023)
The sharing economy has been growing at an unprecedented rate in recent years. Digital peer-to-peer platforms have facilitated this growth and the ease of use and accessibility of these platforms have led to their increased adoption. Peer-to-peer platforms have expanded their services to new countries which has enabled consumers to participate in various sharing economy services globally. With the increasing popularity of the sharing economy, there is a growing need to understand why and how consumers participate in these platforms. The aim of the study is to explore the factors that motivate consumers to rent an accommodation via peer-to-peer digital platform and examine the extent to which cultural factors, and travel destination influence their decision-making process. The study was conducted as qualitative research and the data was collected through semi-structured interviews. A total of 10 interviews were conducted amongst young Finnish consumers who had prior experience with accommodation rentals through the accommodation sharing platform Airbnb. The study was further supported by a literature review, which provides the theoretical framework for the study. The literature review focuses on the extant research on sharing economy, motivation theories, generation Z and cultural values as well as the relationship between these topics. The findings of the study show that cost benefits were found to be the most prominent factor guiding purchase decisions, followed closely by convenience whereas social and sustainability factors were considered less influential in the decision-making process. Authenticity and uniqueness of the accommodation were also found to be important factors for some participants. Additionally, the study found that trust was a crucial factor and reviews played a vital role in building trust. The impact of travel destination on sharing economy participation was found to be influenced by cultural differences and safety concerns in cases where the travel destination was perceived to be culturally highly distinct or located far away.

Jakamistalous on kasvanut viime vuosina ennennäkemätöntä vauhtia. Digitaaliset vertaisverkkoalustat ovat toimineet kasvun tukena ja muun muassa alustojen helppokäyttöisyys ja saavutettavuus on nähty alustojen käytön yleistymiseen vaikuttavina tekijöinä. Vertaisverkkoalustat ovat laajentaneet palvelujaan uusiin maihin, mikä on mahdollistanut sen, että kuluttajat voivat hyödyntää jakamistalouden alustoja ja palveluita maailmanlaajuisesti. Jakamistalouden suosion kasvaessa tarve ymmärtää, miksi ja miten kuluttajat käyttävät vertaisverkkoalustoja lisääntyy. Tutkimuksen tavoitteena on tutkia tekijöitä, jotka motivoivat kuluttajia vuokraamaan majoituksen digitaalisen vertaisverkkoalustan kautta sekä selvittää, missä määrin kulttuuriset tekijät ja matkakohde vaikuttavat kuluttajan päätöksentekoprosessiin. Tutkimus toteutettiin laadullisena tutkimuksena ja aineisto kerättiin puolistrukturoiduilla haastatteluilla. Haastatteluja toteutettiin yhteensä kymmenen ja haastateltavat koostuivat nuorista suomalaisista kuluttajista, joilla oli kokemusta majoitusvuokrauksesta Airbnb:n kautta. Tutkimuksen tukena käytettiin myös kirjallisuuskatsausta, joka muodostaa tutkimuksen teoreettisen viitekehyksen. Kirjallisuuskatsauksessa keskitytään jakamistaloutta, motivaatioteorioita, Z-sukupolvea ja kulttuurisia tekijöitä käsitteleviin aikaisempiin tutkimuksiin ja teorioihin. Tutkimuksen tulokset osoittavat, että kustannushyödyt ovat merkittävin ostopäätöstä ohjaava tekijä majoituspaikan valinnassa. Toisena tärkeänä tekijänä nähtiin kätevyyteen liittyvät tekijät, kun taas sosiaalisilla ja kestävään kehitykseen liittyvillä tekijöillä koettiin olevan vähemmän merkitystä päätöksentekoprosessissa. Myös majoituspaikan autenttisuus ja ainutlaatuisuus osoittautuivat tärkeiksi tekijöiksi joidenkin haastateltavien osalta. Lisäksi tutkimuksessa havaittiin, että luottamus on merkittävä tekijä majoituspaikan valinnassa ja arvosteluilla on huomattava rooli luottamuksen rakentamisessa. Kulttuurierot ja huoli turvallisuudesta olivat tutkimuksessa havaittuja kohdemaan vaikutukseen liittyviä tekijöitä, joita esiintyi erityisesti sellaisissa tapauksissa, joissa kohdemaan koettiin olevan maantieteellisesti etäällä tai kulttuurisesti kaukana omasta kotimaasta.
Keywords: fi=Kansainvälinen liiketoiminta|en=International Business|; Master's Degree Programme in International Business